Seeing, hearing, feeling and acting: Brazil and the SUS from the perspective of medical students - Soares, Lisa Ananda Rodrigues; Luna , Davi Mendes; Gualberto, Iana Dayse Nogueira; Silva , Julia Leone Leite Morais; Montenegro , Marcela Vasconcelos; Evangelista , Rodrigo Carneiro de Farias; Caliari , Vitoria de Ataide; Barros, Maria da Neves Dantas da Silveira (Seven Editora, 2024)
Despite the progress in primary care coverage, the Unified Health System faces the challenges of guaranteeing health care in a country of continental dimensions marked by significant social inequality. Based on the above, medical students carried out a qualitative study that aimed to broaden the view of primary care and the practice of semiology in a different scenario from that experienced in Brazilian medical schools, expanding the horizons of medical education to other social realities. Three families from the municipality of São Benedito do Sul, recognized for having a low human development index and being an endemic area for neglected diseases, were randomly selected. Sociodemographic and clinical data were obtained through anamnesis, physical examination, capillary glucose collection and electrocardiogram, the latter for screening for Chagas disease. Future doctors were able to see, hear and feel the reality of a portion of the population that is on the margins of public policies. The need to reformulate the medical curriculum to deal with this reality was evidenced, based on the teaching of the values of clinical examination and alternative medicine based on the use of natural resources to modify this situation. DOI:https://doi.org/10.56238/sevened2024.026-061